Advances in visual informatics : 4th International Visual Informatics Conference, IVIC 2015, Bangi, Malaysia, November 17-19, 2015, proceedings /: 4th International Visual Informatics Conference, IVIC 2015, Bangi, Malaysia, November 17-19, 2015, proceedings. (2015) - Unknown
No abstract available